Analisis Faktor Yang Mempengaruhi Kecemasan Pada Pasien Hemodialisis: Literatur Review - Ni Luh Emilia; Rosyidah Arafat; Elly Lilijanty Sjattar (Jurnal Keperawatan Muhammadiyah, 2020)
Purpose of this literature review writing is to analyze factors that influence anxiety of hemodialysis patients.Method that was used in gathering article was using several electronic databases including PubMed, Proquest, Ebsco Host and Google Scholar, reference sources were taken manually, with limitations on articles published from 2015 - 2020, with relevant keywords.Results obtained were 7 articles that have been adjusted to the inclusion criteria of 5 articles were cross-sectional research and 2 articles were observational cross-sectional research. This study  stated several factors that can cause or trigger patients anxiety  with hemodialysis, namely age, sex, education, finance, retirement, cohesiveness, social support and length of stay.Conclusion of anxiety is a problem that can be experienced by patients who are undergoing hemodialysis and it can occur due to several factors that need to be detected earlier to get the right intervention.Keywords:  Anxiety,  Dialysis, Haemodialysis, Hemodialysis (HD)